A Feasibility Study on Disasters and Disaster Risk Reduction Factors Awareness of LSPU Students - Daran, Danilo S.; Briones, Mario R.; Alvarez, Manuel Luis; Ampo, Richard C.; M. Reyes, Mary Grace; Cabigan, Victoria; Aquino, John Michael (Indonesian Journal Publisher in cooperation with Indonesian Social Studies Association (APRIPSI), 2022)
This study determined the students' degree of awareness at Laguna State Polytechnic University (LSPU) Sta. Cruz, Laguna in terms of disaster risk reduction and its significance, which was the basis of the LSPU DRRM Center construct. This employed a descriptive- correlational study and used a purposive sampling technique. The results revealed that the respondents had experienced various types of disasters. They are slightly aware, at least, of risk reduction factors anchoring on political commitment, while they are no less than slightly aware of the particulars related to risk reduction measures. Moreover, the results of χ² Tests of Independence revealed that the awareness of Disaster Risk Reduction Factors depends on the individual's exposure to a single or a combination of natural disasters. On the contrary, the extent of awareness of those factors does not depend on the respondent's exposure or experience with global viral diseases and man-made disasters.